True Touches of Nature: Laurence Sterne and the Sacred Heart - Miller, Eric (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2022)
The pulse-taking scene in Laurence Sterne’s 1768 Sentimental Journey Through France and Italy is representative of the fiction. The episode, in which Yorick palpates the wrist of a Parisian grisette or shopgirl, engages with both literal and figurative matters of the heart. Scholars have long speculated about what Sterne may have meant when he described Sentimental Journey as a “work of redemption.” None has connected Yorick’s discourse of sensibility to a contemporary Catholic controversy of which, circumstantial evidence suggests, Sterne may have been aware. This controversy could well have informed the Anglican Sterne’s equivocal rapprochement with Catholic practice. In 1765, Pope Clement XIII approved some measure of devotion to the Sacred Heart of Jesus. He thus gave credence to the visions of the nun Marguerite-Marie Alacoque, which occurred between 1673 and 1675. After the second Jacobite uprising, in the late 1740s, the young Sterne had joined with his rabidly anti-Papist uncle Jacques to prosecute the nuns of Micklegate Bar outside York, who occupied one of only two convents left in England. In Sentimental Journey, which develops its own tragicomic theory of the Sacred Heart, Sterne may make eccentric amends for his former zealotry.